2013
DOI: 10.1158/0008-5472.can-12-1472
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Lyn and the Atypical Kinase SgK269/PEAK1 in a Basal Breast Cancer Signaling Pathway

Abstract: Basal breast cancer cells feature high expression of the Src family kinase Lyn that has been implicated in the pathogenicity of this disease. In this study, we identified novel Lyn kinase substrates, the most prominent of which was the atypical kinase SgK269 (PEAK1). In breast cancer cells, SgK269 expression associated with the basal phenotype. In primary breast tumors, SgK269 overexpression was detected in a subset of basal, HER2-positive, and luminal cancers. In immortalized MCF-10A mammary epithelial cells,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
150
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(154 citation statements)
references
References 34 publications
4
150
0
Order By: Relevance
“…This suggests that these proteins are paralogs, and the three homologous regions undertake critical conserved functions. Previously, we demonstrated that overexpression of SgK269 in MCF-10A-immortalized mammary epithelial cells perturbed cell phenotype and signaling in a manner consistent with SgK269 functioning as a breast cancer oncogene (11). To interrogate the function of specific regions of SgK269, we generated a series of deletion mutants lacking the N-terminal segment (⌬N), the CH region (⌬CH), and the pseudokinase domain (⌬PK) (Fig.…”
Section: Identification Of Sgk269 Domains Critical For Its Function Inmentioning
confidence: 99%
See 3 more Smart Citations
“…This suggests that these proteins are paralogs, and the three homologous regions undertake critical conserved functions. Previously, we demonstrated that overexpression of SgK269 in MCF-10A-immortalized mammary epithelial cells perturbed cell phenotype and signaling in a manner consistent with SgK269 functioning as a breast cancer oncogene (11). To interrogate the function of specific regions of SgK269, we generated a series of deletion mutants lacking the N-terminal segment (⌬N), the CH region (⌬CH), and the pseudokinase domain (⌬PK) (Fig.…”
Section: Identification Of Sgk269 Domains Critical For Its Function Inmentioning
confidence: 99%
“…SgK269 Y1188 binds Shc1 and mediates a key switch in EGF receptor signal output over time, from mitogenic/survival signaling to that regulating morphogenesis (10). In addition, SgK269 couples to the Ras signaling pathway via Tyr-635-mediated binding to the Grb2 SH2 domain (11). Overexpression of SgK269 in mammary epithelial cells promotes a partial epithelial-mesenchyme transition and aberrant growth and morphogenesis in 3D Matrigel culture, identifying SgK269 as a potential breast cancer oncogene (11).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative tyrosine phosphorylation profiling of docetaxel-sensitive and resistant cells was undertaken by immunoaffinity purification followed by liquid chromatography/tandem mass spectrometry (LC/MS-MS) in combination with stable isotope labeling with amino acids in cell culture (SILAC), as previously described (19,20).…”
Section: Phosphoproteomic Profilingmentioning
confidence: 99%